ANALISIS STRATEGI PENAWARAN KONTRAKTOR UNTUK MEMENANGKAN TENDER ONLINE DI DENPASAR - I NENGAH SUBAGIA; I GUSTI AGUNG AYU ISTRI LESTARI; PUTU FENDY PRADITHA (Universitas Mahasaraswati Mataram, 2020)
This study aims to analyze the strategies and factors that influence and obstacles faced by contractors to win online tenders. The method used is to use a quantitative method through the distribution of questionnaires to agencies that won an online tender for the Government Project for Bina Marga in Denpasar City in the period 2017-2019 with the qualifications of a small class contractor (K). Data in this study were obtained through Denpasar City LPSE (secondary data) and questionnaire data that had been filled out by service providers (primary data). Both data are processed using the IBM SPSS Statistics 23. The results of the data analysis are the strategies and factors that influence the online bid winnings are maximizing the completeness of the letters and documents requested, the suitability and authenticity of the documents requested, availability, level of education and personnel experience and expert certification. or skilled so that service providers can pass to the next stage, the methods and strategies of implementation and control used and the workforce to be placed on the work package to be tendered. The dominant obstacle in participating in online tenders in LPSE is the completeness of documents and bids